Temporal Patterns of Influenza A and B in Tropical and Temperate Countries: What Are the Lessons for Influenza Vaccination? - Caini, Saverio (2016)
Fil: Caini, Saverio. Netherlands Institute for Health Services Research (NIVEL), Utrecht; Paises Bajos.